Portrait of Hatchery Management Profile on Rainbow Fish Melanotaenia boesemani (Allen & Cross, 1980) Cultivation in Jakarta Area - Nugraha, Media Fitri Isma; Avarre, Jean-Christophe; Pouyaud, Laurent; Kadarusman, Kadarusman; Carman, Odang; Junior, M. Zairin (Torani Journal of Fisheries and Marine Science, 2018)
Hatchery managers and maintaining genetic diversity and fitness population in endangered and threatened species in pond is a important and difficult thing to do.  But is must to do for conservation biology.  Fitness and structure population depends on effective breeding number (Ne) and population connectivity between each other. The second most important thing is gene flow and genetic drift. Ne is major role in the maintenance of genetic diversity as indicator for inbreeding depresion and genetic drift.  We sampled 6 hatchery in Jakarta  and Bekasi Indonesia region and used 12 polymorphic microsatellite loci to quantify population genetic structure. Result in this study are, each farm have different methode. The old farmers is bapak Gusi and bapak Hasan (+30 years).  Ne in bapak Hasan and bapak Gusi hatchery is 66,667 and F value is 0,00749 and loosing allele (P) is 0,26183.  Compared with younger farmers bapak Yahya (5 years) have Ne = 133,333, F = 0,00375 and P = 0,06855.  Even though hatchery bapak Hasan and bapak Gusi have the same value Ne, F and P but the result in population structure they are different founder populations. Hatchery bapak Hasan have unique structure and alleles composition compared with other hatchery.Keywords: breeding, management, Melanotaenia boesemani, hatchery, population.